Barriers and enablers to deprescribing benzodiazepines in older adults: elaborating an instrument and validating its content - Luciana Soares Rodrigues; Marlon Silva Tinoco; Luanna Gabriella Resende da Silva; Clareci Silva Cardoso; Luana Carolaine Campos de Sousa; Ana Maria Rosa Freato Gonçalves; André Oliveira Baldoni (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVE: To elaborate and validate an instrument on barriers and enablers to deprescribing benzodiazepines in the patient's perspective. METHODS: This study was conducted in 3 stages: (1) a methodological stage, (2) a semi-structured pilot interview with 25 older adults undergoing clonazepam deprescribing, and (3) content validation with the Delphi technique. Content validation was performed by 50 specialists with degrees and/or experience with primary health care and/or health care of older adults, such as physicians, pharmacists, and nurses. For evaluating the obtained results, we analyzed the concordance of evaluations with the coefficient of content validity (CCV). We considered values equal to or higher than 0.8 as acceptable levels of concordance. RESULTS: The instrument was considered validated in the first round of evaluation, where all items obtained a CCV of more than 0.8 in the specialists' assessment. Nevertheless, they proposed improvements that were incorporated to the final version of the questionnaire. CONCLUSION: The instrument represents an important tool to be used by health care professionals for optimizing benzodiazepine deprescribing, with suitable levels of clarity and validity.